A Descriptive Examination of Prisonization through the Lens of Post-Exoneration Offending. Issue 8 (3rd August 2018) - Shlosberg, Amy; Ho, Aaron; Mandery, Evan
ABSTRACT: Prisonization, which seeks to explain criminal behavior as a function of past prison experiences, has been examined through many lenses; however, more novel approaches to exploring prisonization have been lacking. This study uniquely explores the concept of prisonization by describing the post-release behavior of 118 wrongfully convicted individuals, known as exonerees. Conclusions were drawn from a dataset of exonerees and criminal history background searches. Comparative analyses show that exonerees without priors serve longer sentences and demonstrate a shorter time to failure (as measured by post-release offending). Offending among this cohort may suggest that otherwise law-abiding citizens were negatively affected by their experience in prison and, furthermore, may indirectly support the notion that being imprisoned fosters criminality in individuals. These results can support conceptual and practical advancements.